2020
DOI: 10.20883/medical.405
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the skin NADH changes during ischaemia and reperfusion in humans

Abstract: Nicotinamide adenine dinucleotide (NADH/NAD+) is involved in many important biochemical reactions in human metabolism, including participation in energy production by mitochondria. Flow Mediated Skin Fluorescence (FMSF) is a non-invasive method to study dynamic changes in the content of the reduced form of NADH by measuring the optical properties of NADH related to the emission of the autofluorescent light (460 nm) after an earlier excitation by ultraviolet light. This review summarises the available studies u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, the total amount of NAD (sum of NADH and NAD+) should remain stable over a short time in our experiment. 23 Thus we may indirectly conclude on the NAD+ content.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, the total amount of NAD (sum of NADH and NAD+) should remain stable over a short time in our experiment. 23 Thus we may indirectly conclude on the NAD+ content.…”
Section: Discussionmentioning
confidence: 98%
“…21,47 We have previously reported that the brachial artery's occlusion increases the intensity of skin 460-nm fluorescence accompanied by a cessation of microvascular blood flow as measured by laser Doppler. 18,23 During reperfusion, the restoration of arterial blood flow to the forearm causes an immediate increase in the microvascular blood flow with a short, approximately 20-second, hyperaemic response. Although the 460-nm fluorescence drops instantly at the beginning of reperfusion, this signal's intensity does not recover to the baseline level for over 2-5 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations